Vragen des Tijds (Haarlem: H.D. Tjeenk Willink)
"Vrijzinnige Werkmansbibliotheek Leren VereertRedactie: H. Goeman Borgesius, W. Heineken, S. Van Houten, A. Kerdijk, B.H. Pekelharing, J.W. Straatman, J. D. Veegens, F. Domela Nieuwenhuis, P. Van Geer"